Antimicrobial Activity of Selected Indian Medicinal Plants - C.M. Karrunakaran, D. Venkatesan, (Journal of Phytology, 2010)
The traditional medicine still plays a important role in the primary health care, three Indian medicinal plants Aegle marmelos, Solanum nigrum and Cassia fistula were extracted by soxhlet extraction method. These three plant materials were subjected to preliminary phytochemical screening activity against Gram negative organism of Escherichia coli (NCIM: 2065) and gram positive organism of Staphylococcus aureus (NCIM: 2079) and they were compared with control drug Penicillin at different concentrations at 0.5, 1.0, 1.5, 2.0, and 2.5 mg/ml by disc diffusion method. At higher concentration of 2.5mg/ml Cassia fistula exhibits maximum zone of inhibition of about 30.9mm against Staphylococcus aureus, and is considered as susceptible. Such that zone of inhibition not found in Aegle marmelos and Solanum nigrum, and are considered as resistant. In case of Escherichia coli, Solanum nigrum exhibits maximum zone of inhibition of about 30.1mm such zones are not found in Aegle marmelos and Cassia fistula, and are considered as resistant and control drug penicillin shows less activity compared to the plant extract Aegle marmelos, Solanum nigrum, and Cassia fistula